The urgency to expand the antiviral indications of general chronic hepatitis B patients - Fan, Ping; Li, Lan-Qing; Chen, En-Qiang (Frontiers in Medicine, 2023)
In recent years, liver experts have conducted in-depth discussions on whether it is necessary to expand the indication of antiviral therapy for patients with chronic hepatitis B (CHB). Currently, the guidelines are too strict in treating CHB patients. With the deepening understanding of the natural history of hepatitis B virus infection, there is more and more evidence challenging the view that there is no disease progression and no treatment in the immune tolerance period and inactive period. As the price of antiviral agents for CHB has decreased significantly, the availability of antiviral agents for CHB has been considerably improved. Therefore, expanding the indications for antiviral treatment of CHB is of great significance in achieving the goal of eliminating the public health threat of viral hepatitis by 2030, as the World Health Organization has proposed.